If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 3z + -8 + -5z = 0 Reorder the terms: 14 + -8 + 3z + -5z = 0 Combine like terms: 14 + -8 = 6 6 + 3z + -5z = 0 Combine like terms: 3z + -5z = -2z 6 + -2z = 0 Solving 6 + -2z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -2z = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -2z = 0 + -6 -2z = 0 + -6 Combine like terms: 0 + -6 = -6 -2z = -6 Divide each side by '-2'. z = 3 Simplifying z = 3
| x^2-25=144 | | 11y-14=7+14y | | 16x^2-25x=-9 | | 6x-6=3(x-2) | | 5w+10=2(4w+10) | | 1h+h=9 | | Y+3-28= | | w^2+12w-20=0 | | 3(x+2)=7(2x-1) | | 3w+10=3w+10 | | f(x)=3x^2+7x-5 | | 5y-19=12 | | 10x+9y=1200 | | 9p+7=6p+5 | | f(3)=3x^2-4x+5 | | 3ln(x+3)=-6 | | 2n-12=3n+9 | | (x+69)+2x=180 | | 10=5m(m-5) | | 8w+12=180 | | x^2-(-5)x+c=0 | | -122=2x-7(-3x-22) | | -15.00+0.39x=14.95+0.13 | | f(-2)=3x^2-4x+5 | | x^2-2x+y^2-6y-27=0 | | 9-5y=14 | | 9-5y=12 | | -6(5-2x)=-8 | | 9q^2-71q-36=0 | | 2(x^2)=2r^2 | | (0.3)(0.07)=x | | 5(x+x)=720 |